MULTILATERAL DIPLOMACY AND ITS POSITION ACCORDING INTERNATIONAL AND DIPLOMATIC LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Multilateral diplomacy slowly but surely leads us to democratization ofinternational society, developing its own machinery, techniques owncharacteristic "language" and professional ethics.The undoubtedly fact that multilateral diplomacy seeks to accomplishtasks that are of great importance to all of us as individuals, whileachieving its greatest benefit among almost all international subjects,overcoming the differences between them, show us the benefits ofmultilateral diplomacy.